Gene Expression Profiling and Regression Rate of Irradiated Uveal Melanomas - Rao, Rajesh C. (Ophthalmic Surg Lasers Imaging Retina, 2015)
BACKGROUND AND OBJECTIVE: Uveal melanoma (UM) is the most common primary intraocular cancer, however the molecular features that predict response to therapy are poorly understood. Our objective was to determine whether gene expression profiling (GEP) is associated with rate of tumor regression following I-125 plaque brachytherapy for UM. METHODS: Retrospective review of 138 patients with posterior UM treated with I-125 plaque brachytherapy in which GEP class and 3-month post-radiation ultrasonographic tumor thickness were available. Statistical analysis was performed using T-test and Fisher’s exact test. RESULTS: GEP class assignment was class 1 in 83 (60.1%) and class 2 in 55 (39.9%) patients. Mean patient age was 60.9 years for class 1 and 68.1 years for class 2 tumors (P=0.002). Mean initial tumor diameter was 13.0 mm for class 1 and 14.1 mm for class 2 tumors (P=0.02). Mean initial tumor thickness was 5.2 mm for class 1 and 6.1 mm for class 2 tumors (P=0.047). Mean reduction in tumor thickness at 3-month post-radiation 26.5% for class 1 and 16.7% for class 2 tumors (P=0.03) after I-125 plaque radiotherapy. CONCLUSION: Class 1 tumors exhibit more rapid early tumor regression than class 2 tumors following I-125 plaque radiotherapy.